2016
DOI: 10.1073/pnas.1615832113
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary switches between two serine codon sets are driven by selection

Abstract: Serine is the only amino acid that is encoded by two disjoint codon sets so that a tandem substitution of two nucleotides is required to switch between the two sets. Previously published evidence suggests that, for the most evolutionarily conserved serines, the codon set switch occurs by simultaneous substitution of two nucleotides. Here we report a genome-wide reconstruction of the evolution of serine codons in triplets of closely related species from diverse prokaryotes and eukaryotes. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…Further, the assumption that all mutations have the same transversion-transition rate might exacerbate the tendency to misinterpret MNM-produced nonsynonymous changes as evidence for positive selection. Although CMDs might also be driven to fixation by recurrent positive selection [40][41][42] , these considerations suggest that the possibility that failing to incorporate MNMs in likelihood models might make tests of adaptive evolution susceptible to false positive inferences. The BS and related tests might be particularly sensitive to this problem because they seek signatures of positive selection acting on individual codons on individual branches of the tree 11,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the assumption that all mutations have the same transversion-transition rate might exacerbate the tendency to misinterpret MNM-produced nonsynonymous changes as evidence for positive selection. Although CMDs might also be driven to fixation by recurrent positive selection [40][41][42] , these considerations suggest that the possibility that failing to incorporate MNMs in likelihood models might make tests of adaptive evolution susceptible to false positive inferences. The BS and related tests might be particularly sensitive to this problem because they seek signatures of positive selection acting on individual codons on individual branches of the tree 11,43 .…”
Section: Introductionmentioning
confidence: 99%
“…From triplets of genomes with reliable phylogenetic relationships that were extracted from the ATGC database 17,27 , we obtained frequencies of double and single substitutions in codons, and in double synonymous controls (see Methods for details). The key difference between the present work and the previous studies is that all the analyses included comparison to double synonymous substitutions that served as null models for the double substitutions in codons.…”
Section: Resultsmentioning
confidence: 99%
“…The control for mutation biases was achieved by comparing the DF for codon double substitutions to those of double synonymous substitutions. Previously analyzed codon double substitutions in serine codons 17 and in stop codons 16 suggested that these changes are under positive selection due to elevated double substitution frequencies compare to the expectation from single substitutions. Our focus here was to infer the type of selection by using more adequate controls, namely equivalent synonymous double substitutions, in order to address the possibility that apparent selection affecting codon double substitutions was due to mutational biases as previously suggested 9,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in rationalization were reduced when only the Ser, Gly and Pro attributions could be interpreted as a coherent group. The 'enigma' of the two Ser codes, which could not be explained in any of the previous studies [25,26], now receives an understanding based on dimer complementariness. The indication that the Gly and Pro codes would also have belonged to an unforeseen pair (Table 1) found support only when the interpretation provided by the metabolic pathways of amino acid biosynthesis entered the argument.…”
Section: Hydropathy Correlationmentioning
confidence: 93%